Combination of different perspectives in strategy formulation - KARAOULANIS, ANDREAS (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
In this paper the author tries to outline some major strategy guidelines in terms of internal or external factors by following the paths of certain authors such as Porter, Dawar, Eisenhardt and Sull and Mankins. The author mainly focus on strategy to performance gap and strategy communication inside the company in order to underline their vast importance in formulating the companys strategy implementation.